PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PERANGKAT DESA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA KANTOR DESA JANGKAR DAN DESA PALANGAN KABUPATEN SITUBONDO - Arrasyd, Humam Mujib; Karnadi, Karnadi; Minullah, Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Jangkar Village and Palangan Village are government organizations responsible for the administration of local government affairs and the interests of the local community in the tasks of development, order, peace, and supervision of regional development. The purpose of this study is to analyze and test the influence of leadership style and work environment on the performance of village officials with work motivation as an intervening variable in the Jangkar Village and Palangan Village Offices in Situbondo Regency. This research is explanatory research using non-probability sampling techniques. Data analysis and hypothesis testing in this study use the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the hypothesis testing for direct effects using the Smart PLS 3.0 application indicate that leadership style has a significant influence on work motivation, the work environment has a significant influence on work motivation, leadership style does not have a significant influence on performance, the work environment does not have a significant influence on performance, and work motivation has a significant influence on performance. The results of the hypothesis testing for indirect effects show that the leadership style variable on performance through work motivation has a positive but not significant influence, while the work environment on performance through work motivation has a significant positive influence.